RBFOX3/NeuN is dispensable for visual function - Lin, Yi-Sian (PLoS One, 2018)
RBFOX3/NeuN is a neuronal splicing regulator involved in neural circuitry balance, as well as neurogenesis and synaptogenesis. Rbfox3 is expressed in neurons; however, in the retina, expression is restricted to cells in the ganglion cell layer and some cells of the inner nuclear layer. Rbfox3 is expressed in a layer-specific manner in the retina, which implies a functional role, however, the role of RBFOX3 in the retina is unknown. Rbfox3 homozygous knockout (Rbfox3(-/-)) mice exhibit deficits in visual learning; therefore, understanding the role of RBFOX3 in the retina is critical for interpreting behavioral results. We found Rbfox3 expression was developmentally regulated in the retina and specifically expressed in ganglion cells, amacrine cells and horizontal cells of the retina. We demonstrate deletion of Rbfox3 resulted in a reduction in the thickness of the inner plexiform layer of the retina, where synapses are formed. Number of ganglion cells and amacrine cells is normal with loss of Rbfox3. Innervation of retinal ganglion cells into their targeted brain regions is normal in Rbfox3(-/-) mice. Importantly, Rbfox3(-/-) mice displayed normal non-image and image forming functions. Taken together, our results suggest RBFOX3 is dispensable for visual function.